Gestantes con obesidad y su percepción del proceso de parto - María Dolores López Medina; Ana Belén López Araque; Rosa María Murillo Castro (Ene, 2015)
Obesity is a risk factor during pregnancy and is associated with several problems during it. Because of that our aim is to know what feeling generates the birth moment in obese pregnant women, it has been conducted a qualitative methodology, type phenomenological, conducting 9 semi-structured interviews with pregnant women with obesity in health area of Valdepeñas. We have conducted a discourse analysis of the women interviewed. The results were fear about the birth moment in primiparous and fear about newborn in secundiparous. As a conclusion we have to say that health professionals should encourage the use of support strategies during pregnancy in order to provide comprehensive care to promote the health of pregnant and puerperal women.